In vitro nuclear receptor inhibition and cytotoxicity of hydraulic fracturing chemicals and their binary mixtures. (May 2018) - Bain, Peter A.; Kumar, Anu
Abstract: The widespread use of hydraulic fracturing (HF) in oil and gas extraction operations has led to concern over environmental risks posed by chemicals used in HF fluids. Here we employed a suite of stable luciferase reporter gene assays to investigate the potential for selected HF chemicals or geogenics to activate or antagonise nuclear receptor signalling. We screened three biocides (bronopol [BP], glutaraldehyde [GA], and tetrakis(hydroxymethyl)phosphonium sulfate [THPS]), a surfactant (2-butoxyethanol), a friction reducer (polyacrylamide), and a coal seam geogenic ( o -cresol) for their potential to act as agonists or antagonists of the estrogen receptor, androgen receptor, progesterone receptor (PR), glucocorticoid receptor or peroxisome proliferator-activated receptor gamma (PPARγ). None of the chemicals induced luciferase activity in any of assays used in the study. In antagonistic mode, BP, GA and THPS caused reductions in luciferase activity in the reporter assays at higher concentrations (50–100 μM), while at low concentrations (2–10 μM) GA and THPS enhanced luciferase activity in some assays relative to controls. None of the other tested chemicals exhibited antagonism in the selected assays. In most cases, altered receptor signalling only occurred at concentrations exhibiting cytotoxicity. However, PPARγ activity, and to a lesser extent PR activity, were inhibited by THPS at sub-cytotoxic concentrations. The majority of binary combinations tested exhibited significantly less-than-additive cytotoxicity, and none of the combinations exhibited synergistic cytotoxicity. In summary, the results of the present study indicate that the selected chemicals are not likely to function as direct agonists of the nuclear receptors tested, and only one chemical, THPS was an apparent partial antagonist of two nuclear receptors. Graphical abstract: Highlights: Six hydraulic fracturing chemicals were screened for nuclear receptor activity. Cytotoxicity was assessed in parallel in order to validate antagonism. No receptor agonism was observed for the chemicals tested. Receptor antagonism by three chemicals was mostly due to cytotoxic effects. Once chemical, THPS, inhibited receptor signalling at sub-cytotoxic concentrations.